2004
DOI: 10.1677/joe.0.1810401
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thyrotropin-releasing hormone receptor in immortalized beta-cell lines and rat pancreas

Abstract: Thyrotropin-releasing hormone (TRH), a hypothalamic tripeptide, is expressed in pancreatic islets at peak levels during the late gestation and early neonate period. TRH increases insulin production in cultured -cells, suggesting that it might play a role in regulating pancreatic -cell function. However, there is limited information on TRH receptor expression in the pancreas. The aim of the present study was to explore the distribution of the TRH receptor in the pancreas and its function in pancreatic -cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
1
9
1
Order By: Relevance
“…TRH initiated EGF receptor phosphorylation, which may be through the TRHR1 receptor paracrine effect in ␤-cells. A higher-affinity MT-TRH (TRH analog) induced stronger EGF receptor phosphorylation than native TRH (21), which fits the notion that the TRH stimulation of EGF phosphorylation depends on TRH receptor-activation. TRH binds to its receptor, causing dissociation of the ␣-and ␤␥-G protein subunit and thus triggering signal cascades after GPCR activation (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…TRH initiated EGF receptor phosphorylation, which may be through the TRHR1 receptor paracrine effect in ␤-cells. A higher-affinity MT-TRH (TRH analog) induced stronger EGF receptor phosphorylation than native TRH (21), which fits the notion that the TRH stimulation of EGF phosphorylation depends on TRH receptor-activation. TRH binds to its receptor, causing dissociation of the ␣-and ␤␥-G protein subunit and thus triggering signal cascades after GPCR activation (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The delay in the EGF receptor phosphorylation response to TRH compared with EGF indicates that there are several different mechanisms between TRH and EGF for EGF receptor activation. It is unclear whether TRH phosphorylates the EGF receptor through TRHR1 (21) or -R2 (37). TRHR1 has been found in the mouse pancreas, but no references were reported as to but had no effect on Tyr 1068 phosphorylation (middle).…”
Section: Time Course Of Two Egf Receptor Phosphorylation Residues In mentioning
confidence: 99%
“…In contrast, TRH-R2-knockout mice exhibit normal glucose homeostasis even when given a high fat diet. Therefore, TRH regulation of glucose metabolism in rodents (Kulkarni et al , 1995; Yamada et al , 2000; Luo and Yano, 2004) is mediated by TRH-R1. Furthermore, it was suggested that the effect of TRH on glucose homeostasis is mediated, at least in part, by TRH-R1 expressed on insulin-secreting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, electron microscopy has revealed that TRH is co-localized with insulin in secretory granules in β cells in fetal rat islets (17,18). In contrast, it is controversial whether TRHRs are expressed in the normal pancreas (12,13) even though several lines of evidence suggest a possible pancreatic role for TRHR signaling (19). Perhaps the most compelling data in this regard are the alterations in glucose homeostasis that were observed in TRH-knockout mice (20) that are consistent with the idea that the TRH/TRHR system plays a role in embryonic development or adult function of β cells, or both.…”
Section: Introductionmentioning
confidence: 99%